FACTORS AFFECTING USER SATISFACTION ON e-FILING SYSTEM IN INDONESIA - Fathimatus Zahro Fazda Oktavia (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
One of the electronic tax systems used in Indonesia is e-Filing which results in an increase in the number of users. However, the high intensity of using the system does not guarantee that the system is successful and fully supports user needs. This study was conducted to determine the determinants of e-Filing user satisfaction by adopting several models of measuring system success formulated by Delone and Mclean. This research contributes to measuring and providing improvements to the entire tax information system in Indonesia. The study was conducted using a survey method (questionnaire) and purposive sampling on 562 lecturers of the State Polytechnic of Malang. Using the multiple linear regression statistical method and in accordance with the hypothesis in the study, the results showed that partially System Quality, Information Quality and Service Quality had a positive effect. and significant to User Satisfaction. In addition, simultaneously System Quality, Information Quality and Service Quality have a positive and significant effect on User Satisfaction.